The Kinetics of manganese removal from bore well water using Katalox Light, Birm and ISR - Sah, Chandan Kumar Sah; Amatya, Iswar Man (Journal of Innovations in Engineering Education, 2021)
Groundwater scarcity and quality degradation has been a pertinent issue in Kathmandu Valley (KV). The high concentration of Manganese in the groundwater is the major issue in the drinking water quality. This research work presents the removal Manganese through comparative study between Katalox light filtration model (KLFM) and Rapid sand filtration model (RSFM) at three different flow rates. Gravel, Katalox light, Burgess Iron Removal Method (BIRM), Iron Specific Resin (ISR) and sand are commonly used filter media for KLFM and RSFM respectively. KLFM filtration is physio-catalytic adsorption purification process of high removal capacity of Manganese at higher pH. Two identical filter columns packed with Katalox light 1.24mm size (depth 96.52cm), ISR 0.56mm size (depth 5.1cm), BIRM 1.23mm size (depth 38.1cm) and sand 0.57mm size (depth 60cm) were used and operated at three discharges viz., 0.018L/s, 0.020L/s and 0.022 L/s at Manohara-Besi Water Supply Committee located in Changunarayan Nagarpalika, Bhaktapur and detailed study was conducted. As the influent raw Manganese concentration varied up to of 0.672mg/L, the effluent Mn concentration was found to be 0.024mg/L, 0.026mg/L and 0.044mg/L in KLFM and 0.542mg/L, 0.534mg/L and 0.628mg/L in RSFM at 0.018L/s, 0.020L/s and 0.022L/s respectively. The average Manganese removed at 0.018L/s, 0.020L/s and 0.022L/s were found to be 96.000%, 95.785% and 93.388% in KLFM and 10.500%, 9.507%, and 6.612% in RSFM of influent average Manganese concentration respectively. The Manganese removal was found to be more effective at flow rate of 0.018L/s. KLFM and RSFM Filters were backwashed with backwashing velocity of 24 m/h with periodic 10-15minutes and 36m/h within 3 days respectively, when the terminal head loss of 215.7cm and 219cm was obtained and both filters were run in parallel for 1.5 hours daily. It was concluded that the KLFM media could be a good media for the reduction of Manganese concentration.